Toward an Integrated Authentic Material Design Model for EFL Skill Development and Communicative Competence - Nur Annisa Fitri; Nayla Sa'adah; Irma Irma; Safarina Hidayati; Faradila Faradila; Hesty Widiastuty (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
This study integrates theoretical and empirical approaches to the design of instructional materials for teaching English as a Foreign Language (EFL) that cover the four skills of listening, speaking, reading and writing. This research, using the qualitative, library-based synthesis method, systematically compiles and reviews published scholarly books, journal articles, and empirical studies (2010 to 2025) and applies qualitative content analysis, coding and thematic synthesis. The analysis has surfaced three core tenets of effective material design for EFL: authenticity, systematically integrated scaffolding, and learner-centred integration. These tenets assert that EFL instruction, even when framed as a series of discrete lessons, contextually taught and integrated with other skills, results in improved communicative competence and enhanced language transfer. This research study affords EFL teaching, curriculum development, and material design practitioners for face-to-face and online modalities the opportunity to expand their paradigms. The research is unique with the proposal of the Integrated Authentic Material Design Model (IAMDM) that brings together authenticity, scaffolding, and learner centredness as a single theoretical construct that serves to bridge theory and practice while enhancing the pedagogical knowledge of EFL teachers and material developers.